Grid-based problem solving environments [electronic resource] : IFIP TC2/WG 2.5 Working Conference on Grid-based Problem Solving Environments : implications for development and deployment of numerical software, July 17-21, 2006, Prescott, Arizona, USA - IFIP TC2/WG 2.5 Working Conference on Grid-based Problem Solving Environments (2006 : Prescott, Ariz.); Gaffney, P. W. (Pat W.); Pool, James C. T., 1937-; IFIP Working Group 2.5--Mathematical Software (Boston, MA : International Federation for Information Processing, 2007)
57